Atrioventricular Node Ablation in Langendorff-Perfused Porcine Hearts Using Carbon Ion Particle Therapy. (April 2015) - Lehmann, H. Immo; Richter, Daniel; Prokesch, Hannah; Graeff, Christian; Prall, Matthias; Simoniello, Palma; Fournier, Claudia; Bauer, Julia; Kaderka, Robert; Weymann, Alexander; Szabó, Gábor; Sonnenberg, Karin; et al.
<x xml:space="preserve">Abstract</x> Background— Particle therapy, with heavy ions such as carbon-12 (12C), delivered to arrhythmogenic locations of the heart could be a promising new means for catheter-free ablation. As a first investigation, we tested the feasibility of in vivo atrioventricular node ablation, in Langendorff-perfused porcine hearts, using a scanned 12C beam. Methods and Results— Intact hearts were explanted from 4 (30–40 kg) pigs and were perfused in a Langendorff organ bath. Computed tomgraphic scans (1 mm voxel and slice spacing) were acquired and 12C ion beam treatment planning (optimal accelerator energies, beam positions, and particle numbers) for atrioventricular node ablation was conducted. Orthogonal x-rays with matching of 4 implanted clips were used for positioning. Ten Gray treatment plans were repeatedly administered, using pencil beam scanning. After delivery, positron emission tomography-computed tomgraphic scans for detection of β+ (11C) activity were obtained. A 12C beam with a full width at half maximum of 10 mm was delivered to the atrioventricular node. Delivery of 130 Gy caused disturbance of atrioventricular conduction with transition into complete heart block after 160 Gy. Positron emission computed tomgraphy demonstrated dose delivery into the intended area. Application did not induce arrhythmias. Macroscopic inspection did not reveal damage to myocardium. Immunostaining revealed strong γH2AX signals in the target region, whereas no γH2AX signals were detected in the unirradiated control heart. Conclusions— This is the first report of the application of a 12C beam for ablation of cardiac tissue to treat arrhythmias. Catheter-free ablation using 12C beams is feasible and merits exploration in intact animal studies as an energy source for arrhythmia elimination.